Effect of an educational intervention on human papillomavirus (HPV) knowledge and attitudes towards HPV vaccines among healthcare workers (HCWs) in Western China. Issue 2 (1st February 2021) - Chen, Hui; Zhang, Xi; Wang, Wei; Zhang, Rong; Du, Mei; Shan, Li; Li, Yucong; Wang, Xiaohui; Liu, Yijun; Zhang, Wen; Li, Xiaoling; Qiao, Youlin; et al.
ABSTRACT: Background: Healthcare workers (HCWs) play a key role in the recommendation of HPV vaccination. Our study aimed to understand to what extent a structured health intervention could change the knowledge and attitudes toward HPV and its vaccines among HCWs in Western China. Methods: This was a multi-center, questionnaire-based interventional study conducted across 12 cities of seven provinces in Western China, from November 2018 to July 2019. Participants were recruited from local health systems by e-invitation. Questionnaires were administered to participants before and after the intervention. Results: A total of 1448 HCWs attended the educational lectures and 1354 participants completed both pre- and post-study questionnaires. In general, HCWs had satisfactory baseline knowledge regarding HPV and its vaccines compared with other populations, and a significantly higher knowledge level was observed after the intervention. However, some more specific knowledge on the vaccination procedures, other HPV-related diseases and whether HPV testing was required before vaccination was relatively poor. Following the educational intervention, the correct responses to the above questions increased ( P < .001). However, it was still lower compared with answers to other questions. Change was also detected regarding HCWs' willingness to recommend HPV vaccines to the appropriate population ( P < .001). Conclusion: Educational intervention on HPV and its vaccines is effective in improving HCWs' knowledge levels and willingness to recommend HPV vaccines. Future educational interventions should focus more on knowledge regarding HPV-related diseases and HPV vaccination. Education campaigns targeting rural HCWs are urgently needed in the near future.